Effects of Total Suspended Solids at Different Levels on the Eggs and Larvae of Endemic Fish, Tarek (Alburnus tarichi Güldenstädt, 1814) in the Karasu River (Van, Turkey) - Ataman Altuğ Atıcı; Mahmut Elp; Fazıl Şen (Aquatic Sciences and Engineering)
The Karasu River (Van, Turkey) is one of the most important sources of intensive reproduction for Tarek (Alburnus tarichi Güldenstädt, 1814) in the Van Lake basin. However, sand pits and sand extraction activities in the Karasu River threaten the spawning areas of A. tarichi. This study aimed to investigate how increased sediment concentration in the Karasu River affects the eggs and larvae of A. tarichi during the reproductive period. The study in the laboratory was designed by measuring total suspended solids and turbidity associated with the river over two years for five different experimental groups (corresponding to 0, 10, 50, 100, and 600 mg L-1, and associated groups: control group, Group 1, Group 2, Group 3, and Group 4, respectively). The percentage of hatched out larvae was statistically different between the groups (p<0.05). The highest percentages of hatched out larvae were found in the control group (73.98±5.89%) and Group 1 (68.05±2.96%). The highest survival rates in larvae were determined in the control group (53.35±5.62%) and Group 1 (44.98±4.41%). These results demonstrate that A. tarichi is sensitive to suspended solid concentrations that are very common in the natural environment. In conclusion, sand pits and sand extraction activities must be stopped completely during the reproductive period of A. tarichi between May and July and strict controls should be put in place during this time. These measures will provide an important contribution to ensuring the continuity of this species.